Charge state manipulation of silicon-based donor spin qubits - Lo Nardo, R (2015)
Spin properties of donor impurities in silicon have been investigated by electron spin resonance (ESR) techniques for more than sixty years. These studies gave us a contribution towards understanding some of the physics of doped semiconductor materials in general, which is the platform for much of our current technology. Despite the fact that donor electron and nuclear spins have been researched for so long, ESR studies of their properties are still giving us interesting insights. With the introduction of the concept of quantum information in the 1980s, some properties of donor spins in silicon, that were known from the fifties (such as long relaxations), have been reinterpreted for their potential application in this field. Since then, incredible experimental results have been achieved with magnetic resonance control, including manipulation and read-out of individual spins. However, some open questions are still to be answered before the realisation of a spin-based silicon quantum architecture will be achieved. Currently, ESR studies still contribute to help answering some of those questions. In this thesis, we demonstrate electrical and optical methods for donor charge state manipulation measured by ESR. Recent experiments have demonstrated that coherence time of nuclear spins may be enhanced by manipulating the state of donors from neutral to singly charged. We investigate electric field ionisation/neutralisation of arsenic donors in a silicon SOI device measured by ESR. Below ionisation threshold, we also measure the hyperfine Stark shift of arsenic donors spins in silicon. These results have, for instance, implications on how fast individual addressability of donor spins may be achieved in certain quantum computer architectures. Here, we also study optical-driven charge state manipulation of selenium impurities in silicon. Selenium has two additional electrons when it replaces an atom in the silicon crystal (i.e. double donor). The electronic properties of singly-ionised selenium make it potentially advantageous as spin qubit, compared to the more commonly studied group-V donors. For instance, we find here that the electron spin relaxation and coherence times of selenium are up to two orders of magnitude longer than phosphorus at the same temperature. Finally, we demonstrate that it is possible to bring selenium impurity in singly-charged state and subsequently re-neutralise them leaving a potential long-lived 77Se nuclear spin.